IoT Based Novel System for Drainage and Irrigation Water Management: Efficient Reusing of Drainage Water for Irrigation (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The most significant and helpful technique for the management of waste water is to efficientreusing of it. This can be implemented by developing a system that reuses maximum of drainage water.For short and long term needs, it is important to stay away from the misuse of water. In some regions,percentage of rain is minimum, in such areas reuse of sewage water is generally significant and helpfulstrategy. As per the quality of drainage water, this water can be utilized for the irrigation purpose withnecessary water purification process. For salt sensitive crops it is not possible to reuse the drainagewater, so it is necessary to purify and reuse this water. If this project is situated close to the wet-landthen the drainage water can be reused efficiently for it. This research work presents a system to measurethe water level of drainagecanal and pumps it to the necessary irrigation area. This systems consists ofwater level point contact sensor, solenoid valve, Wi-Fi module, Arudino microcontroller.